Infrastructural Being Rethinking dwelling in a naturecultural world - Valkonen, Jarno; Kinnunen, Veera; Huilaja, Heikki; Loikkanen, Teemu (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book provides a comprehensive insight into the contemporary naturecultural world by exploring infrastructures through the dwelling approach. The notion of naturecultures has been utilized in environmental humanities and social sciences to emphasize the inherent messiness of the lived world and the inseparability of social and biophysical elements. Concept of naturecultures stresses that seemingly "natural" is always simultaneously "cultural" and vice versa. This approach allows fleshing out the messy engagements with infrastructures, which in this book is conceptualized as infrastructural being. This book is a contribution to emerging discussions on infrastructures in the fields of environmental social sciences and humanities. It sensitizes to the peculiarities of modern dwelling and modern, yet often overlooked, ways of being connected with nature. Moreover, it provides tools for speculating, how could things be otherwise. The book is a topical response to the urgent call for developing new forms of human-nature relations in times of environmental turbulence. Jarno Valkonen is a professor of Sociology at the University of Lapland, Finland. His wide-ranging research interests include politics of nature, human-environment relationality, and indigenous knowledge. Recently, his research has focused on waste governance, Circular Economy, and infrastructures. Veera Kinnunen (Ph.D.) is a sociologist and a cultural historian at the University of Oulu. She is working on a threshold of more-than-human sociology, environmental humanities, and feminist ethics. Her research interests cover material culture of everyday life, dwelling, and waste. Heikki Huilaja (Ph.D.) is a researcher in sociology at the University of Lapland. His main research interests cover work and labor market, with a particular emphasis on recruitment and evolution of skills. In the area of waste studies, Huilaja's focus is on waste as a source of employment and business opportunities and on the societal organization of waste in Finnish Lapland. Teemu Loikkanen (MSocSc) is a junior researcher at the University of Lapland. In his ongoing doctoral research, he explores the position of citizens in Circular Economy waste management by developing the concept of waste citizenship.
Introduction: Naturecultural imagination in the times of environmental damage -- Approaching infrastructural being -- Anticipatory Infrastructures, Emerging Technologies and Visions of Energy Futures -- Assembling Wild Nature: Icelandic Wildness as a Natureculture Meshwork -- The Social Class and Lifestyle Embeddedness of Being Within Energy Infrastructures -- Circular economy as infrastructural change - waste citizenship in the bin -- Everyday infrastructures of care: unmaking waste through repairing and composting -- The Biosphere and the Garden: Nature as Infrastructure? -- Afterword: Some unintentional consequences of infrastructure.
Keywords: Environmental sciences-Social aspects; Science-Social aspects; Human ecology; Sociology; Environmental Social Sciences; Science and Technology Studies; Environmental Anthropology; Sociology